Compressive strength of mortar containing cockle shell waste as mixing ingredient - Khairunisa, Muthusamy; Rahimah, Embong; Rajan, Jose; Nabilla, Mohamad; Nur Syahira Hanim, Kamarul Bahrin (IOP Publishing, 2021)
Undesirable pollution issue posed by disposal of shells from cockle trade and greenhouse gases release by cement industry requires solution. In view of cleaner environment, reducing waste dumped could be achieved through utilization of shell waste in cement production. In line with sustainable construction concept, production of construction material that contains lesser natural resources and combined with existing solid waste is more environmentally friendly. In relation to that, transforming the cockle shell waste into a value-added item such as partial cement replacement in construction material would reduce waste disposed to the environment. An experimental work was carried out to investigate the effect of cockle shell powder as a material for partial cement replacement on compressive strength and water absorption of mortar. Powdered cockle shell of 0%, 10%, 20%, 30% and 40% were integrated as partial cement replacement. Air curing method were used for all specimens. Specimen were subjected to compressive strength and water absorption test. The finding shows that incorporation of 10% cockle shell powder enhances compressive strength of mortar and reduces the percentage of water absorbed.